Kirigami‐Inspired Pressure Sensors for Wearable Dynamic Cardiovascular Monitoring (Adv. Mater. 36/2022). Issue 36 (8th September 2022) - Meng, Keyu; Xiao, Xiao; Liu, Zixiao; Shen, Sophia; Tat, Trinny; Wang, Zihan; Lu, Chengyue; Ding, Wenbo; He, Ximin; Yang, Jun; Chen, Jun
Abstract : Pressure Sensors In article number 2202478, Jun Yang, Jun Chen, and co‐workers report a kirigami‐inspired pressure sensor for wearable dynamic cardiovascular monitoring. Utilizing the vertical kirigami‐inspired structure and a simple fabrication process, the sensor provides an ascendant way to overcome motion artifacts when monitoring human pulse signals, thus representing a solid advancement toward personalized cardiovascular monitoring in the era of the Internet of things.